2023
DOI: 10.3390/educsci13040353
|View full text |Cite
|
Sign up to set email alerts
|

How Should We Teach Nature Protection? Self-Determination and Environmental Attitudes

Abstract: Environmental attitudes are supportive for learning about the environment and for pro-environmental engagement. The question, then, is how to strengthen and establish environmental attitudes. Based on a sample of 429 middle and high school students, we investigated the effect of self-determination-based motivation on environmental attitude. While high levels of self-determination (i.e., intrinsic motivation) positively affected pro-environmental attitude (β = 0.40), low levels of self-determination (i.e., exte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 57 publications
0
1
0
1
Order By: Relevance
“…We see the potential for three lines of research that could complement the processes depicted in Figure 2. First, recent work drawing on self-determination theory (Deci and Ryan, 2000) has shown that when motivation to engage in stewardship and environmentally responsible behavior is internalized (intrinsic), individual action is significantly more impactful compared to when external incentives (extrinsic) are offered (Cooke et al, 2016;Baierl and Bogner, 2023). In the context of our model depicted in Figure 2, it would likely have implications for individuals' appetite for information (knowledge) and for their understanding and willingness to act (efficacy).…”
Section: Conclusion and Recommendations For Future Researchmentioning
confidence: 99%
“…We see the potential for three lines of research that could complement the processes depicted in Figure 2. First, recent work drawing on self-determination theory (Deci and Ryan, 2000) has shown that when motivation to engage in stewardship and environmentally responsible behavior is internalized (intrinsic), individual action is significantly more impactful compared to when external incentives (extrinsic) are offered (Cooke et al, 2016;Baierl and Bogner, 2023). In the context of our model depicted in Figure 2, it would likely have implications for individuals' appetite for information (knowledge) and for their understanding and willingness to act (efficacy).…”
Section: Conclusion and Recommendations For Future Researchmentioning
confidence: 99%
“…Интегрированная и, в меньшей степени, идентифицированная и внутренняя мотивации положительно связаны с проэкологическими аттитюдами (Pelletier et al, 1998). Согласно результатам другого исследования, интроецированная, внутренняя и, в меньшей степени, интегрированная мотивации положительно связаны с проэкологическими аттитюдами, в то время как конструкт «включение природы в себя» (Liefländer et al, 2013), интеркоррелирующий со связью с природой (Brügger et al, 2011), положительно связан со всеми внутренними формами мотивации и в меньшей степени -с внешней мотивацией (Baierl, Bogner, 2023).…”
Section: взаимосвязи между конструктамиunclassified